186k views
5 votes
Simplify these expressions. a. 2r + 3 + 4r b. 8 + 3d + d c. mn + (–3mn) + 6 d. 10s + (–10) + (–4s)

2 Answers

6 votes

Answer:

a) 3 + 6r

b) 8 + 4d

c) 6 - 2mn

d) -10 + 6s

Explanation:

Combine all like-terms:

d) 10s + -10 + -4s

-10 + 6s

c) mn + -3mn + 6

6 - 2mn

b) 8 + 3d + d

8 + 4d

a) 2r + 3 + 4r

3 + 6r

I am joyous to assist you anytime.

User Sealla
by
6.7k points
4 votes

Answer:

a) 6r + 3

b) 8 + 4d

c) -2mn

d) 6s - 10

Explanation:

a) 2r + 3 + 4r

We need to add the like terms

= 2r + 4r + 3

= 6r + 3

b) 8 + 3d + d

We need to add the like terms

= 8 + 3d + d

= 8+4d

c) mn + (–3mn)

We need to add the like terms

= mn - 3mn

= -2mn

d) 10s + (–10) + (–4s)

We need to add the like terms

= 10s –10 –4s

= 10s - 4s - 10

= 6s - 10

User Kit Menke
by
6.3k points